2017
DOI: 10.3391/ai.2017.12.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Impact of invasive quagga mussel (Dreissena rostriformis bugensis, Bivalva: Dreissenidae) on the macroinvertebrate community structure of a UK river

Abstract: A review of the scientific literature and an analysis of unpublished material identified ~ 50 possible alien molluscs from Greece, four of which were newly reported here. Records of ~ 100 additional taxa, which would strongly inflate the alien species numbers, were excluded. Among the ~ 50 candidate species, 43 were confirmed as alien and 12 as cryptogenic. Twenty-nine alien species were considered established, and four deemed invasive. Our results are consistent with the position of Greece in the east-west Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Roy et al, (2014) for example, concluded the potential impact, risk of arrival and risk of establishment of quagga mussels, Dreissena rostriformis bugensis, in the UK to be the highest out of 93 species examined. As predicted, the quagga mussel was detected in the UK later the same year (Mills et al, 2017). Quagga mussels are one of a number of Ponto-Caspian INNS that are currently spreading throughout Europe, including the UK.…”
Section: Introductionsupporting
confidence: 56%
“…Roy et al, (2014) for example, concluded the potential impact, risk of arrival and risk of establishment of quagga mussels, Dreissena rostriformis bugensis, in the UK to be the highest out of 93 species examined. As predicted, the quagga mussel was detected in the UK later the same year (Mills et al, 2017). Quagga mussels are one of a number of Ponto-Caspian INNS that are currently spreading throughout Europe, including the UK.…”
Section: Introductionsupporting
confidence: 56%
“…The abundance of net building caddisfly was positively associated with quagga mussel density in the Wraysbury River (Hydropsyche spp. ; Mills et al, 2017). This effect may also be non-linear; Albertson et al (2014) found that at high densities, the stabilization of river gravels by polycultures of multiple caddisfly species was greater than the expected additive effects…”
Section: Quagga Mussels Increase Critical Entrainment Shear Stressmentioning
confidence: 99%
“…(2) the density of mussels present in the Wraysbury River (determined by a preliminary survey; 135 mussels m À2 ), and (3) a likely invasion scenario (270 mussels m À2 ). Quagga mussel density at the time of collection (135 mussels m À2 ; August 2021) had increased by 150% since 2016 (mean 54 mussels m À2 ; Mills et al, 2017), with invasive population densities frequently exceeding 1000 mussels m À2 (Nalepa et al, 2009;Strayer et al, 1999). Therefore, 270 mussels m À2…”
Section: Experimental Treatmentsmentioning
confidence: 99%
“…Where this occurs in natural environments, change to invertebrate community structure beyond that observed directly via crayfish predation may result. This is because bivalves can comprise over 50% of total benthic invertebrate biomass (Burlakova, Karatayev, & Padilla, 2005;Mills, Chadwick, & Francis, 2017) and are considered a keystone group for community function (Geist, 2010;Lopes-Lima et al, 2014;Lydeard et al, 2004).…”
mentioning
confidence: 99%